Pneumatic dispensing of aqueous Al₂O₃ suspensions via material extrusion additive manufacturing - Flavie Lebas; Sylvain Marinel; Christelle Bilot; Romuald Herbinet; Loïc Le Pluart; Charles Manière (Next Materials)
Material extrusion, also known as Robocasting or Direct Ink Writing (DIW) is an efficient and eco-friendly additive manufacturing method for fabricating large and thick ceramic components, such as alumina. While screw-based extrusion is the prevalent approach due to its precise control over printing parameters, pneumatic-based extrusion is gaining attention for its suitability in automated processes and reduced handling requirements. However, pneumatic extrusion faces challenges, primarily the narrower range of printable rheological behavior. Achieving a balance between extrudability and the self-supporting capacity of printed structures is critical. Moreover, bubble elimination, easily addressed in screw-based extrusion, remains a significant challenge in pneumatic systems. To overcome these issues, optimal concentrations of dispersants, ceramic loading, and additives were determined to achieve the desired shear-thinning rheological properties suitable for pneumatic extrusion. Additionally, this study, by employing a rapid one-step ball milling method for suspension preparation, is somewhat unique, providing a streamlined alternative to traditional processes. A degassing study was conducted to minimize bubble formation, ensuring print quality. Using the optimized parameters, including extrusion pressure and layer height, complex structures were successfully printed. After sintering at 1450 °C, the samples exhibited a 99.5 % dense microstructure with an average grain size of 1.71 µm. The alumina demonstrated excellent mechanical properties, achieving a hardness of 2094 HV at 1450°C, which is well aligned with the literature.